2011
DOI: 10.1016/j.vetmic.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of respiratory infection patterns of breeding sows in five farrow-to-finish herds

Abstract: A longitudinal study was carried out in five French farrow-to-finish herds differently affected by respiratory diseases to describe the carrying and infection patterns of batches of sows to various respiratory pathogens during gestation and lactation. An entire batch of sows was followed during two successive reproduction cycles. Nasal, tonsillar and oro-pharyngeal swabs and blood samples were taken from each sow 9 and 4 weeks before farrowing and 1 and 4 weeks after farrowing. Mycoplasma hyopneumoniae, Actino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 21 publications
3
41
0
1
Order By: Relevance
“…Thus, it is termed porcine respiratory disease complex (PRDC) (1). Often primary viral agents, such as porcine reproductive and respiratory syndrome virus, porcine circovirus type 2, and swine influenza virus (SIV), lead to damage of the mucociliary barrier and a decreased immune response, predisposing pigs to secondary infections and pneumonia by opportunistic bacterial pathogens, such as Pasteurella multocida, Mycoplasma hyopneumoniae, and Streptococcus suis (3). However, very little is known about interactions between viral and bacterial pathogens and their role in the copathogenesis of such complex diseases.…”
mentioning
confidence: 99%
“…Thus, it is termed porcine respiratory disease complex (PRDC) (1). Often primary viral agents, such as porcine reproductive and respiratory syndrome virus, porcine circovirus type 2, and swine influenza virus (SIV), lead to damage of the mucociliary barrier and a decreased immune response, predisposing pigs to secondary infections and pneumonia by opportunistic bacterial pathogens, such as Pasteurella multocida, Mycoplasma hyopneumoniae, and Streptococcus suis (3). However, very little is known about interactions between viral and bacterial pathogens and their role in the copathogenesis of such complex diseases.…”
mentioning
confidence: 99%
“…It is common to find members of the Pasteurellaceae family as well as some Gram-positive bacteria such as S. suis [63], with virus like a PRRSV and SIV, they are common microorganisms in the porcine respiratory complex and the presence of some of them as the PRRSV, facilitates the colonization of the respiratory tract by other pathogens [1] [14]. So, the combination of the respiratory pathogens founded in this study, are most frequently pathogens found in pigs under intensive breeding system [5]. However in relation to the existence of these pathogens in the environment surrounding the animals, few studies exist, so there is no data to compare with these findings.…”
Section: Discussionmentioning
confidence: 98%
“…In this type of production, under normal conditions, the animals are concurrently infected by one or more respiratory viral or bacterial pathogens [1]- [3]. Respiratory diseases in pigs are the main health problem affecting the pork industry today, produce up to 50% mortality in farms, resulting in great economic losses [4] [5]. Only in United States, Porcine Reproductive and Respiratory Syndrome virus (PRRSV) produces losses of $560 million yearly.…”
Section: Introductionmentioning
confidence: 99%
“…PRRSV tends to circulate within a herd, due to the persistent PRRSV infection of carrier animals and the continual availability of susceptible animals by their commingling with infected animals in later stages of production (Zimmerman et al 2006). The sow population constitutes a reservoir for a continuous circulation of respiratory pathogens and needs to be properly considered in control strategies (Fablet et al 2011). Therefore, some PRRSV-infected gilts that entered the breeding population in this farm may actually re-introduce the virus in that population.…”
Section: Journal Of Applied Animal Research 301mentioning
confidence: 99%